2022
DOI: 10.1007/s11356-022-18612-5
|View full text |Cite
|
Sign up to set email alerts
|

A modified cyanobacteria prediction model based on cellular automata model using N and P concentration reverse data: a case study in Taihu Lake

Abstract: The problem of algal bloom caused by eutrophication has attracted global attention. Many scholars have studied the problem associated with algae bloom, but few have carried out dynamic monitoring, instead focusing on the formation mechanism of cyanobacteria. For our study of the Taihu Lake in China, we used Moderate-Resolution Imaging Spectroradiometer (MODIS) and Landsat remote sensing image data from 2017 to establish a prediction model. First, we used MODIS data to retrieve the concentration of N, P, and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recently, the algal blooms in Taihu Lake show certain spatial differences and are affected by environmental factors, human activities near the lake and hydrodynamic conditions (Zhang, Hu, et al, 2020). For example, previous studies have reported that due to significant differences in nutrient (especially N and P) concentrations in different regimes of Taihu Lake, the impact of sediment release on algal blooms at various stretches of the lake is stated to be different (Zhao et al, 2022). Therefore, real‐time monitoring (in situ) and long‐term prediction of algae blooms are vital for freshwater conservation and restoration (Rolim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the algal blooms in Taihu Lake show certain spatial differences and are affected by environmental factors, human activities near the lake and hydrodynamic conditions (Zhang, Hu, et al, 2020). For example, previous studies have reported that due to significant differences in nutrient (especially N and P) concentrations in different regimes of Taihu Lake, the impact of sediment release on algal blooms at various stretches of the lake is stated to be different (Zhao et al, 2022). Therefore, real‐time monitoring (in situ) and long‐term prediction of algae blooms are vital for freshwater conservation and restoration (Rolim et al, 2023).…”
Section: Introductionmentioning
confidence: 99%